2022
DOI: 10.1108/oir-06-2021-0295
|View full text |Cite
|
Sign up to set email alerts
|

Brand post popularity on Facebook, Twitter, Instagram and LinkedIn: the case of start-ups

Abstract: PurposeWith the growing trend of omni-channel marketing, brands are increasingly looking to offer a seamless experience to their online fan base by connecting with them across multiple social media platforms. This paper explores the relationship between brand posts' characteristics and popularity for start-ups across four different social media platforms: Facebook, Twitter, Instagram and LinkedIn.Design/methodology/approachA total of 1,200 social media posts from 10 start-ups were subjected to content analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…A study conducted using Twitch, a live streaming platform, showed that streamers' response to viewer chat contributes to the formation of a user's bond and induces engagement (Jodén and Strandell, 2021). Meanwhile, Robson and Banerjee (2022) confirmed that the effect of brand interaction on the user engagement varies from platform to platform.…”
Section: Theoretical Frameworkmentioning
confidence: 70%
“…A study conducted using Twitch, a live streaming platform, showed that streamers' response to viewer chat contributes to the formation of a user's bond and induces engagement (Jodén and Strandell, 2021). Meanwhile, Robson and Banerjee (2022) confirmed that the effect of brand interaction on the user engagement varies from platform to platform.…”
Section: Theoretical Frameworkmentioning
confidence: 70%
“…Future research could expand the scope of data collection to include multiple social media platforms. The emerging marketing literature on consumer engagement across multiple social media platforms [30,31] could be brought to bear. Moreover, with a larger sample size, there is a need to better understand potential interaction effects among the message characteristics in predicting rebuttal virality.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, gift managers should adopt appearance popularity appeals carefully to avoid over- or under-estimating the effects on online purchase intention. Marketers should also consider the appearance popularity appeals to let givers feel unique and different and produce a unique identity in the social identity process through extraordinary or exaggerated gifts (Robson and Banerjee, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Under this circumstance, popularity appeals provided information regarding general social proof, which acts as social norms that drive buying behavior (Boratto et al, 2021;Goldstein et al, 2008) and meets the minimum standards for the recipient's satisfaction with the gift (Cheng et al, 2021;Jang et al, 2015;Ku et al, 2012). Scholars have discussed that popularity appeals affect consumers' purchase intention (Robson and Banerjee, 2022;Steinhart et al, 2014) and, compared popularity and scarcity appeals to influence buyers' decisions (Das et al, 2018;Wu and Lee, 2016). On investigating (brand) popularity appeal from the marketer's perspective, they found that appearance popularity appeal is common and promotes buyers' decisions (Ghiassaleh et al, 2020;Hofmann et al, 2021;Kim, 2018), which is normally explored in the self-purchase aspect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation